Addition of Lead (Pb)-Nitrate Filler on Polymer Composite Aprons for X-Ray Radiation Shielding - E. Afrianti; D. Tahir; B. Y. E. B Jumpeno; O. A. Firmansyah; J. Mellawati (Atom Indonesia, 2021)
Radiation shielding aprons are needed by radiation workers to minimize radiation exposure to the body. The aprons at present use fabric-coated lead plates which are heavy and rigid materials and therefore are not comfortable to use. Polymer aprons from cassava starch and glycerin with addition of Pb-nitrate filler at 0 %, 2 %, 4 %, and 6 % have been synthesized. Mixtures for synthesizing the polymer apron composites were heated using a magnetic stirrer at a speed of 800 rpm at 160 °C for 25 minutes. Then, the polymer apron composites were dried in an oven for 24 hours at 70 °C. The effectiveness of the apron was determined by calculating the attenuation coefficient (μ), half-value layer (HVL), and radiation absorption. The mechanical properties of the aprons were characterized by testing their tensile strengths using anA&D MCT-2150 universal tester. The result shows that the optimal addition of Pb-nitrate filler of as much as 6 % produced aprons with an attenuation coefficient of 1248 cm‑1, HVL of 0.54 cm, and radiation absorption of 25 %, while the aprons’ tensile strength was obtained as28.244 MPa. The addition of Pb-nitrate as a filler in apron composites proportionally improves the quality of materials used as radiation shields. More detailed research is still needed to obtain the best apron.